Effektivitas Ibadah Dalam Pengembangan Kecerdasan Spiritual Santri, Di Pondok Pesantren Suryalaya Tasikmalaya - Basukiyatno; Fitriyanto (Cakrawala: Jurnal Pendidikan, 2020)
This study aims to determine the education system developed in the Pondok Pesantren Suryalaya Tasikmalaya. Pesantren is one of the oldest educational institutions in Indonesia. Pesantren, according to the analysis of Nurcholis Madjid (1985), is an institution that embodies the process of developing national education naturally. Historically, pesantren contained not only Islamic meaning, but also Indonesian authenticity, because similar institutions existed during the Hindu-Buddhist rule, while Islam continued and Islamized it. In line with the nature of Islamic boarding school education that grows and develops entirely based on religious motivation, Pesantren Suryalaya was developed to streamline religious broadcasting efforts and practice of its teachings. In its implementation, pesantren education carries out a process of building knowledge, attitudes, and skills concerning religious aspects. The main objective is to seek the formation of virtuous people (al-akhlaq al-karimah) with consistent religious practices (istiqomah). A santri (student) in a pesantren according to Marzuki Wahid (1999: 17) must also carry out the function of finding the ultimate truth, as Sufis wander to get 'food' for their insatiable soul. Therefore, salafiyah pesantren do not provide certificates, the expected output is to give birth to devout people (whole human beings). Ketaqwaan is believed by pesantren residents as the pinnacle of intelligence.